1973
DOI: 10.1172/jci107463
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Prolonged Administration of Ethanol on Cardiac Metabolism and Performance in the Dog

Abstract: A B S T R A C T The effect of prolonged administration of alcohol on mitochondrial function and high-energy phosphate (ATP) of heart muscle was investigated in dogs. Animals were divided into two groups, a control group and a group that received alcohol. In the experimental series, dogs received 400 ml of a 25% solution of alcohol added to the food and drinking water. Measurements were carried out after ethanol had been withheld for 2 days. Total myocardial blood flow, cardiac output, and myocardial 02 consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

1974
1974
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(27 citation statements)
references
References 20 publications
2
24
1
Order By: Relevance
“…In that study, activities of mitochondrial enzymes were all reported as higher in heavy drinkers and were correlated with alterations in functional parameters (e.g., cardiac output). Those results contrast with the results of an earlier study that reported an alcohol-induced depression of mitochondrial respiratory function in cardiac muscle (29). However, differences in study design, such as the species studied and duration of alcohol intake, may account for the contradictory findings.…”
Section: Discussioncontrasting
confidence: 99%
“…In that study, activities of mitochondrial enzymes were all reported as higher in heavy drinkers and were correlated with alterations in functional parameters (e.g., cardiac output). Those results contrast with the results of an earlier study that reported an alcohol-induced depression of mitochondrial respiratory function in cardiac muscle (29). However, differences in study design, such as the species studied and duration of alcohol intake, may account for the contradictory findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Since caloric equivalents were not provided it is difficult to compare these data with the present study; moreover, species difference may exist. In a recent study of dogs fed ethanol in a daily quantity similar to that of the present study, but for a 14-wk period, no hemodynamic abnormality was observed (55). This is consistent with the view that duration of ingestion is an important determinant.…”
Section: Resultssupporting
confidence: 93%
“…Over the past 20 yr, light and electron microscopic changes in mitochondrial structure and function have been documented in myocardium from animals (11,12) and human subjects (13,14) exposed to ethanol. After a lag period of ethanol exposure in vivo, mitochondria isolated from the heart exhibit impaired rates of oxygen consumption, diminished respiratory control, and reduced P/O ratios (15)(16)(17)(18). Although such changes may regress in vivo with cessation of exposures to ethanol, reversibility is not immediate but requires up to 8 wk (17).…”
Section: Methodsmentioning
confidence: 99%
“…Consumption of alcohol over several weeks leads to gross morphological changes in heart mitochondria in laboratory animals (11,12) and human subjects (13,14). Impairment of mitochondrial function has been noted as well and it includes diminished phosphate/oxygen ratios (P/O)' and respiratory control ratios (15)(16)(17)(18); these are changes that do not occur after exposure of mitochondria to ethanol in vitro.…”
Section: Introductionmentioning
confidence: 99%